Finding Nemo - Walters, Graham; Stanton, Andrew; Peterson, Bob.; Reynolds, David; Unkrich, Lee.; Brooks, Albert, 1947-; DeGeneres, Ellen; Gould, Alexander, 1994-; Dafoe, Willem; Garrett, Brad, 1960-; Janney, Allison; Pendleton, Austin; et al. (Burbank, Calif. : Buena Vista Home Entertainment, 2003)
The fretful Marlin and his young son Nemo become separated from each other in the Great Barrier Reef. Nemo, a clown fish, is unexpectedly taken from his home and thrust into a fish tank in a dentist's office overlooking Sydney Harbor. Buoyed by the companionship of a friendly fish named Dory, Marlin embarks on a dangerous trek and finds himself the unlikely hero.
DVD, Region 1 encoding; Dolby digital 5.1 surround EX; THX-certified including THX optimizer; widescreen (1.78:1) and full frame (1.33:1) versions.
In English with optional French or Spanish soundtracks; optional subtitles in French or Spanish; closed-captioned.
Voices: Albert Brooks, Ellen Degeneres, Alexander Gould, Willem Dafoe, Brad Garrett, Allison Janney, Austin Pendleton, Stephen Root, Vicki Lewis, Geoffrey Rush, Elizabeth Perkins.
Directors of photography, Sharon Calahan, Jeremy Lasky ; animators, Brett Coderre ... [et al.] ; art directors, Randy Berrett ... [et al.] ; editor, David Ian Salter ; original music, Thomas Newman.
MPAA rating: G.
Special features: Disc 1: visual commentary, including deleted scenes; "Making Nemo" documentary; the art of Nemo narrated by the artists; turn your TV into a virtual aquarium with scenes from the movie; Disc 2: "Exploring the reef" with Jean-Michel Cousteau and all your Nemo friends; Pixar Animation Studios short film "Knick knack"; a peek at the next Pixar Animation Studios film "The incredibles"; "Fisharades" game; learning fun with "Mr. Ray's encyclopedia"; a behind-the-scenes studio tour.
Keywords: Anemonefishes -- Juvenile drama; Fathers and sons -- Juvenile drama; Aquariums -- Australia -- Sydney (N.S.W.) -- Juvenile drama; Fishes -- Drama; Fathers and sons -- Drama; Aquariums -- Drama; Peces marinos -- Teatro juvenil; Padre e hijo -- Teatro juvenil; Acuarios -- Teatro juvenil; Fishes -- Juvenile drama; Father-son relationship -- Juvenile drama; Aquariums -- Australia -- Sydney (N.S.W.) -- Juvenile drama; Animated films; Video recordings for the hearing impaired